Comparison of two different training interventions on laboratory parameters and race performance in competitive young XCO athletes: a randomized controlled trial - Krauss, I.; Schneeweiss, P.; Ebler, B.; Theobald, U.; Schellhorn, P.; Haigis, D.; Niess, A. (Journal of Science and Cycling, 2017)
Introduction The mountain bike discipline Cross Country Olympic (XCO) is characterized by intermitted intervals. These high intensity demands have further extended lately as race duration has been shortened, race profiles have become more irregular and technical demands of the courses continuously increase1;2. Recent data on adolescent competitive XCO athletes show that 3-min intervals at 120% of the individual anaerobic threshold (IAT) and shorter intervals of approx. 20 seconds at 240% IAT are particularly frequent in XCO2. These and previous findings highlight the importance of anaerobic capacities on race performance3. As a consequence, the current training catalogue for XCO athletes was adapted to account for these specific race characteristics4. It is inspired by the power-based training levels and further differentiates the high intensity training zones to account for the short and medium term high loads of XCO races 2;4;5. These physiological demands should also be mapped in the context of performance testing. In this regard, the importance of short intensity intervals such as the 1-min All-out-time-trial (1-min AOTT) has been demonstrated6. Based on the aforementioned premises the aim of this project was to compare the effectiveness of two different 4-week training protocols on laboratory parameters and race performance. One of the protocols was especially designed to foster high intensity intervals.